Measuring the impact of exchange rate policy on the general level of prices in Algeria for the period 1990-2022 Using a form Ardl - MAHFOUDI FOUAD; MAHFOUDI IBRAHIM EL KHALIL; AIDJOULI KHALED (Journal of North African Economies, 2025)
This study aims to understand the exchange rate and its impact on the general price level in Algeria for the period 1990-2022. It addresses general concepts of the exchange rate and the general price level, and refers to price indices. We employed both descriptive and econometric methodologies in our study, using the ARDL model to address the research problem. We found that the official exchange rate has a negative impact on the general price level in the short term, and there is an inverse relationship between the official exchange rate and the general price level in the long term.